Implications of intensive care unit admissions among medicare beneficiaries following resection of pancreatic cancer. Issue 3 (5th October 2021) - Rice, Daniel R.; Hyer, J. Madison; Tsilimigras, Diamantis; Pawlik, Timothy M.
Abstract: Background: Intensive care unit (ICU) use has increased among patients with cancer. We sought to define factors associated with ICU admissions among patients with pancreatic cancer and characterize trends in mortality among hospital survivors. Methods: The Surveillance, Epidemiology, and End Results (SEER)‐Medicare linked database was used to identify patients with pancreatic cancer who underwent resection. Multivariable analyses were conducted to identify factors associated with ICU admission and mortality among hospital survivors. Results: Among 6422 Medicare beneficiaries who underwent resection of pancreatic cancer, 2386 (37.1%) had an ICU admission. Patients with ICU admissions were more likely to be younger (10‐year increase odds ratio [OR]: 0.83, 95% confidence interval [CI]: 0.77–0.89), male (OR: 1.17, 95% CI 1.05–1.30) and undergo resection at a teaching hospital (OR: 1.19, 95% CI: 1.05–1.36). While the majority of patients survived to hospital discharge ( n = 2106; 88.3%), a majority of patients ( n = 1296; 54.3%) died within 6 months. Among patients who had subsequent ICU admissions, 1‐ and 5‐year survival was only 31.8% and 11.0%, respectively. Conclusions: Over one‐third of patients with pancreatic cancer had an ICU admission. While most patients survived hospitalization, more than one‐half of patients died within 6 months of discharge and two‐thirds died within 1 year. These data should serve to guide patient–provider discussions around prognosis relative to ICU utilization.